Evaluation of learning program subjects for building utility systems based on facilities and infrastructure standards using the CIPPO model at SMK N 2 Banda Aceh - Ahzaliza, Dian; Maksum, Hasan; Wakhinuddin, Wakhinuddin; Indrawan, Eko (Jurnal Pendidikan Teknologi Kejuruan, 2022)
Based on interviews at SMK Negeri 2 Banda Aceh in 2021, obtained from 25 students, 4 people did not pass the skills test in the subject of building utility systems, with an average knowledge score of 79.2 and an average skill score of 78.4 One of the factors is the inadequate infrastructure in carrying out the learning process, especially practicum learning. The purpose of the study was to evaluate the learning process of building utility system subjects in the Construction and Property Engineering Expertise Program using the CIPPO model at SMK Negeri 2 Banda Aceh City. This research is an evaluation research using the CIPPO model, namely the evaluation of the context, input, process, product and outcome. The type of research is a mixed method with Concurrent Triangulation Strategy. Sources of qualitative data were obtained from the Principal, Deputy Principal of the School of Facilities and Infrastructure, Head of the Construction and Property Engineering Expertise Program, Head of Lab and 5. Teachers who teach building utility systems at SMK Negeri 2 Banda Aceh. Quantitative data were taken from 40 students of class XII and XIII. The results showed that the context component was in the sufficient category (73.59%), the Input component was in the sufficient category (75.69%), the process component was in the sufficient category (72.01%), the Product component was in the sufficient category (66.5 %), and the outcome component is also in the sufficient category (73.25%). Because all components are in the sufficient category, it is recommended to make appropriate improvements to improve student achievement abilities in the subject of building utility systems in the Construction and Property Engineering Expertise Program at SMK Negeri 2 Banda Aceh.